Identifying precontact ceramic resource areas in the boreal forest of northern Manitoba, Canada. (January 2019) - Fowler, Kent D; Shabaga, Brandi; Brownlee, Kevin; Fayek, Mostafa
The objective of this study is to better understand how people gained resources to make Middle and Late Woodland pottery from Sipiwesk Lake in northcentral Manitoba. To meet this objective, we conducted petrographic analyses of sediments from Sipiwesk Lake, archaeological sherds from sites around the lake, material from outwashes, fired experimental tiles, and sherds from archaeological sites across the boreal forest ecozone and the prairie ecozone in the south-central and south-western regions of the province. Specimens from each sample were examined using optical petrography, X-ray diffraction, and scanning electron microscopy. Nine distinct fabrics (fired pastes) were identified by correlating the results of these analytical techniques. Each fabric can be considered a "paste recipe" that has local, regional, or pan-regional distributions. Local and regional distribution patterns redefine what "local" production means for mobile hunter-gather communities when the distances people travel for regular and routine seasonal activities are considered. This new model challenges exchange as an explanation for the spatial distribution of pottery. Expanding the range of exploitable distance thresholds for resource acquisition is alone enough to explain why the same pottery compositions would be found over vast areas incorporating one or more river systems. We further suggest that pan-regional recipes resulted from similar practices that served to add, remove, and/or alter the properties of nonplastics in clays. Such practices could potentially frustrate pottery provenience analysis, and we urge further research on the production of experimental pastes and the application of geochemical analyses to precontact Manitoba pottery.